Adaptation cannot keep pace with projected temperature increase - Chen, Shuai; Tan-Soo, Jie-Sheng; Ye, Hai-Jian (Elsevier, 2023)
An emerging argument is that since humans can readily adapt to changing climatic conditions, there is less need to pursue aggressive emissions mitigation strategies. As temperature adaptation is a function of repeated exposure over time, we need empirical approaches that can depict individuals’ temperature history to rigorously examine this claim. Using a longitudinal dataset representative of China, we construct lifetime temperature exposure unique to each individual based on their birth-dates, birth-locations, and movement history. We show that a 1°C increase in individualized temperature anomalies cause a 2% decrease in 1 standard deviation (S.D.) of well-being, where most of the impacts are driven by “hotter-than-expected” weather. In turn, while the adverse impacts of future temperature changes wane after accommodating for adaptation, acclimatization is unlikely to keep pace with future temperature increases except in the net-zero emissions scenario, indicating that stringent greenhouse gas (GHG) emissions cuts are still needed even in this less-pessimistic scenario.